Efektivitas Penyembuhan Luka Bakar Derajat II Sediaan Gel Ektrak Buah Belimbing Wuluh (Averroa bilimbi L.) Terhadap Tikus Jantan Galur Wistar - Astuti , Dina Puji; Fadhilah, Arini (Journal of Pharmaceutical and Sciences, 2025)
Burns are lesions on body tissues that occur due to exposure to heat sources such as fire, chemicals, or electric currents. Bilimbi (Averroa bilimbi L.) is thought to have therapeutic properties to treat burns in male Wistar rats. Burn healing is divided into 3 phases of inflammation, proliferation, and maturation. This study was to prove the ability of the ethanol extract gel preparation of bilimbi in the process of healing burns. Bilimbi extract gel was formulated in three concentration variations, namely 2.5%, 5%, and 10%. Control testing of the preparation included organoleptic, homogeneity, spreadability, viscosity, and adhesion. The bilimbi extract gel preparation with a series of concentrations of 2.5%, 5%, and 10% gave an effect in healing second-degree burns. The percentage data of burn diameter were analyzed using ANOVA. The results of statistical analysis showed that the preparation of ethanol extract gel from star fruit with a concentration of 10% gave a healing effect with a healing percentage of 86% which was almost the same as the positive control. This healing effect is thought to come from the content of star fruit such as alkaloids, flavonoids, saponins.